Effect of different surfactants and thicknesses on electrodeposited films of bismuth telluride and its thermoelectric performance - Kulsi, C. (Institute of Physics Publishing, 2015)
Thin films of bismuth telluride using various surfactants such as sodium dodecyl sulfate (SDS) and polyvinylpyrrolidone (PVP) have been electrochemically deposited. The influence of different surfactants on crystal orientation and morphology was investigated and correlated with the thermoelectric performance of the electrodeposited films. Since thickness affects the thermoelectric performance compared to the surfactant, thickness-dependent thermoelectric performance has also been investigated. The carrier mobilities of the films obtained are significantly enhanced due to improved surface morphology using different surfactants. Between the two surfactants, films with SDS exhibited the higher value of thermoelectric power, power factor, and figure of merit, which is due to the effect of micelle formation. TheXRDpattern of all the films, which are electrodeposited without surfactant or using SDS and PVP, showed preferred crystal orientation along the (018) direction. The roles of organic molecules in the development of nanoparticles with improved thermoelectric properties have been investigated. Â© 2015 IOP Publishing Ltd.